Critical member analysis of wellhead offshore platform due to El Centro earthquake - Leng, Yee Hui (2018)
The paper deals with the seismic analysis of a critical member of wellhead offshore platform in Malaysia with the aim to compute the response and assess the resistance capacity of the structure to earthquake loading. However, the boundary condition of the offshore structure is assumed as fixed to the ground and soil interaction has been neglected. This study is conducted due to tremors occurred in Malaysia caused by Sumatra and Philippine earthquakes have been reported several times. Thus, engineers are concerned about the seismic vulnerability of offshore structures due to lack of earthquake consideration in Malaysia’s building design procedure. With this, wellhead offshore platform is analyzed using Finite Element Modelling (FEM) by SAP2000 software under different types of analyses including Free Vibration Analysis (FVA), Response Spectrum (RS) by using response spectra curves of Eurocode 8 and Time History Analysis (THA) considering El Centro 1940 earthquake data. The design code for the steel frame is Eurocode 3. All the environmental factors data are given such as ranges of wave height, wave period, current velocity and ground motion acceleration. The environmental loadings such as wave and wind load have been designed by referring API (American Petroleum Institute) design criteria. In conclusion, wellhead offshore platform is stable and capable to withstand the earthquake. It can be concluded that the design of the offshore structures can provide sufficient resistance against seismic effects and most of the part of the structure was in good condition.